Sales Growth, Liquidity, and Firm Size on Profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange - Gebi Foresa Lumban Gaol; Arthur Simanjuntak; Rintan Saragih; Robinhot Gultom (Jurnal Ilmiah Accusi, 2026)
This study examines the effect of sales growth, liquidity, and firm size on the profitability of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Profitability is proxied by Return on Assets (ROA). A quantitative causal method with multiple linear regression analysis via SPSS 26 was employed. Purposive sampling yielded 29 companies (82 observations after outlier removal). Results show that sales growth has a positive and significant partial effect on ROA; liquidity has a positive but insignificant partial effect; firm size has a negative and insignificant partial effect; and all three variables simultaneously exert a significant effect on ROA. The Adjusted R² is 0.143, indicating 14.3% of profitability variation is explained by the model